Drug therapy for myocarditis induced by immune checkpoint inhibitors - Wu, Yihao; Xu, Yizhou; Xu, Linhao (Frontiers in Pharmacology, 2023)
Immune checkpoint inhibitors (ICIs), including cytotoxic T-lymphocyte antigen 4 (CTLA-4), programmed cell death 1 (PD-1), and its ligand 1 (PD-L1), have improved the survival in multiple types of cancers; however, ICIs may cause cardiovascular toxicity. Although rare, ICI-mediated cardiotoxicity is an extremely serious complication with a relatively high mortality. In this review, we discuss the underlying mechanism and clinical manifestations of cardiovascular toxicity induced by ICIs. According to previous studies, multiple signaling pathways are involved in myocarditis induced by ICIs. Further, we summarize the clinical trials of drugs for the treatment of ICI-associated myocarditis. Although these drugs have shown the beneficial effects of alleviating cardiac function and reducing mortality rates, their efficacy is not optimal. Finally, we discuss the therapeutic potential of some novel compounds as well as the underlying mechanisms of their action.